Clinical presentation and outcomes in women and men with advanced heart failure. (1st November 2020) - Vishram-Nielsen, Julie K. K.; Deis, Tania; Rossing, Kasper; Wolsk, Emil; Alba, Ana Carolina; Gustafsson, Finn
Abstract: Objective: To examine clinical characteristics and outcomes in women and men referred for advanced heart failure (HF) therapies such as left ventricular assist device (LVAD) or heart transplantation (HTx). Design: A retrospective study of 429 (23% women) consecutive adult HF patients not on inotropic or mechanical circulatory support with left ventricular ejection fraction ≤45% referred for assessment of advanced HF therapies at a single tertiary institution between 2002 and 2016. Clinical characteristics and outcomes were compared in women and men, and all patients underwent right heart catheterization (RHC). Results: At evaluation, women were younger than men (48 ± 13 vs. 51 ± 12 years, p  = .02), and less likely to have ischemic cardiomyopathy. There were no significant differences in NYHA class, contemporary HF therapy use, or physical examination findings, except for lower jugular vein distension and body surface area in women. On RHC, women had lower cardiac filling pressures, but similar pulmonary vascular resistance and cardiac index. Peak oxygen uptake from cardiopulmonary exercise testing was similar in both sexes. At total follow-up time, there were 164 deaths (21% vs. 44%, p  < .0001), 46 LVADs (3% vs. 13%, p  = .005), 110 HTxs (32% vs. 25%, p  = .15), and 82 HTxs without requiring LVAD (29% vs. 16%, p  = .03) in women and men. The time from RHC to HTx (±LVAD) was significantly shorter in women compared to men. Female sex was significantly associated with higher survival independent of time-trend, age, and comorbidities. Conclusion: At evaluation, hemodynamics were less deranged in women. A higher proportion of women received HTx, their waitlist time was shorter, and survival greater.